Mental Skill Tennis Referee: Study On Tennis Referee Asian Games And Asian Para Games Indonesia 2018 - Julian, Rizki; Kristiyanto, Agus; Purnama, Sapta Kunta (Journal of Education, Health and Sport, 2019)
The purpose of this study was to determine the mental skills of tennis referees. This research was conducted on tennis referees in charge of 2018 and Asian Games 2018 Asian Games, assessment tools in the form of questionnaires and interviews that assessed 3 main aspects namely Fundamental skills, Psychosomatic skills, and Cognitive skills, was given to 55 referees from various regions in Indonesia. The results of the study revealed that referees have excellent abilities using mental abilities significantly, referees have very good aspects in terms of goal setting, self-confidence, commitment, controlling fear, concentration, impaired control, imagery, and competency planning but are still low in terms of activation, relaxation, stress reaction, and practice mentally. In improving the mental skill referee quality, there is a need for training to be made on an annual agenda in creating a better referee.